The Archaeology of Art in the American Southwest - Munson, Marit K. (Rowman & Littlefield Publishers, 2011)
Archaeologists seldom study ancient art, even though art is fundamental to the human experience. The Archaeology of Art in the American Southwest argues that archaeologists should study ancient artifacts as artwork, as applying the term 'art' to the past raises new questions about artists, audiences, and the works of art themselves. Munson proposes that studies of ancient artwork be based on standard archaeological approaches to material culture, framed by theoretical insights of disciplines such as art history, visual studies, and psychology. Using examples drawn from the American Southwest, The Archaeology of Art in the American Southwest discusses artistic practice in ancestral Pueblo and Mimbres ceramics and the implications of context and accessibility for the audiences of painted murals and rock art. Studies of Hohokam figurines and rock art illustrate methods for studying ancient images, while the aesthetics of ancient art are suggested by work on ceramics and kivas from Chaco Canyon. This book will be of interest to archaeologists working in the Southwest who want to broaden their perspective on the past. It will also appeal to archaeologists in other parts of the world and to anthropologists, art historians, and those who are intrigued by the material world, aesthetics, and the visual.